Evaluating the Impact of Teaching Aids on English Language Acquisition Among Grade 6 Students - J.F Mirfa; MJF Sujani; MR. Rishad Muhammed; MB Nowzath (Penerbit Hellow Pustaka, 2025)
This research aims to investigate the impact of teaching aids on English language learning among Grade 6 students at KM/KM/Al-Manar Central College, Maruthamunai, focusing on how these aids enhance their learning process and address challenges in acquiring English language skills. The study objectives were; to identify students' difficulties with teaching aids, understand the reasons for their struggles, determine areas requiring more time and practice to develop ESL skills, and propose effective solutions to address issues with descriptive teaching aids. The method used to carry out this research was classroom action research. A Classroom Action Research (CAR) design was employed, incorporating both qualitative and quantitative data collection methods. Primary data was gathered using tests (pre-test and post-test), observations, questionnaires, and interviews, while secondary data was sourced from textbooks, research articles, and reliable websites. Data analysis involved both qualitative approaches (descriptive analysis of observations and interviews) and quantitative methods (statistical analysis of test and questionnaire scores). Various tools, such as tables, graphs, and descriptive forms, were used to present the data. 9 Students were randomly selected as the sample from the total students of 30 students in the class. The data for the research was obtained using observations, interviews, questionnaires, and tests and data was analyzed under quantitative and qualitative methods. The impact of teaching aids on language learning is profound. Research reveals that incorporating multimedia, visual aids, and digital resources into language instruction significantly enhances engagement and comprehension. Teaching aids cater to diverse learning styles, improving vocabulary acquisition, pronunciation, listening, and speaking skills. They foster motivation and active participation, making English language learning enjoyable. However, their effectiveness depends on thoughtful integration and quality design. To maximize language learning outcomes, a balanced approach, merging traditional methods with modern aids, is essential.